Species diversity and abundance of butterfly (lepidoptera: rhopalocera) at different altitudes along the Raub corridor to Fraser’s Hill, Pahang, Malaysia - Suhairiza Suhaimi,; Aisyah Zakaria,; Azman Sulaiman,; Mohd Zabidi Mohd Yaakob,; Mohamad Afiq Aizat Juhary,; Norela Sulaiman, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
This study was conducted to record the butterfly fauna along the Raub Corridor to Fraser’s Hill, Pahang. A series of field samplings was conducted for three consecutive days in October and December 2014, and again from January till March 2015, at three different altitudes, i.e. at 400 to 500 m (lower altitude), 750 to 850 m (middle altitude), and 1000 to 1250 m (higher altitude) within the study area. The butterflies were randomly collected in the day time between 0900-1700 hours by aerial sweeping using the butterfly net. A total of 716 individuals from 138 species in five families (Papilionidae, Nymphalidae, Pieridae, Lycaenidae and Hesperidae) and 14 subfamilies (Papilioninae, Nymphalinae, Satyrinae, Danainae, Morphinae, Coliadinae, Pierinae,Riodininae, Miletinae, Poritiinae, Lycaeninae, Pyrginae, Hesperiinae and Coeliadinae) were recorded. At the higher altitude, the Shannon Diversity Index was H'= 3.683, evenness index, E’=0.5936 and Margalef's Richness Index, R’= 13.0. At the middle altitude, the Shannon Diversity Index was H'= 3.226, evenness index, E’=0.442 and Margalef's Richness Index, R’= 9.756. At the lower altitude, the Shannon Diversity Index was H'= 3.917, evenness index, E’=0.6128 and Margalef's Richness Index, R’= 14.72, respectively. The highest species diversity, species evenness and also species richness indices were recorded at the lowest altitude i.e. 400 to 500 m above sea level.